Pleasures and Pains about Remote Work Experience during the Covid-19 Global Pandemic: A diatextual approach - Mininni, Giuseppe; Manuti, Amelia (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
The Covid-19 global pandemic has radically redesigned social, economic and cultural pivots of human life. Among these, individual professional experience has been completely upset by the introduction of remote/smart working modalities thus imposing workers to fast cope with this great change, adapting to different workloads and time schedules and in some cases even learning new skills. One of the most evident consequence for many people has been a stressful management of the work/family balance, because both life domains required attention and engagement. The consequence being a high perception of overload and a poor quality of life. In view of the above, adopting an applied psycholinguistic perspective, the present study aimed to investigate how individuals made sense of the experience of smart working during phase 2 of the Covid-19 pandemic. Individual in-depth interviews were conducted with a group of 18 workers and diatextual analysis was used to analyze the discursive texture binding the interlocutors to the wider context of talk.